2005
DOI: 10.1007/s00436-005-1371-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of specific and cross-reacting antigens of Fasciola gigantica by immunoblotting

Abstract: Somatic antigens of F. gigantica, G. explanatum, S. spindale and hydatid cyst ingredients were analysed to identify the cross-reactive antigens among them using Western blot technique. When probed with F. gigantica infected cattle sera, the immunodominant 156 kDa and 28 kDa proteins of F. gigantica was found common amongst the antigens prepared from hydatid cysts ingredients like germinal layer, fertile and sterile, hydatid fluid, fertile and sterile, while another protein of 34 kDa was shared between F. gigan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
3
11
1
Order By: Relevance
“…Allam et al (2002) and Gonence and Sarimehmetoglu (2004) in two different studies reported fewer protein bands in SDS-PAGE pattern of Fasciola in comparison to our study. Study of Yokananth et al (2005), about electrophoretic separation of F. gigantica somatic antigen, showed 20 protein bands (ranging from 14 to 156 kDa) (Yokananth et al 2005). Eight protein bands reported in their study are common with those that we are seeing in the current study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Allam et al (2002) and Gonence and Sarimehmetoglu (2004) in two different studies reported fewer protein bands in SDS-PAGE pattern of Fasciola in comparison to our study. Study of Yokananth et al (2005), about electrophoretic separation of F. gigantica somatic antigen, showed 20 protein bands (ranging from 14 to 156 kDa) (Yokananth et al 2005). Eight protein bands reported in their study are common with those that we are seeing in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…It has been shown that sera of cattle, sheep and buffalo, infected with F. gigantica, reacted respectively with 5, 8 and 11 protein bands of F. gigantica somatic antigen (Yokananth et al 2005). In the present study rabbit polyclonal antibodies raised against F. gigantica somatic and ES antigen respectively reacted with 19 and 21 protein bands of F. gigantica somatic antigen.…”
Section: Discussionsupporting
confidence: 57%
“…The affinity purified antigens for Fasciola spp. have shown high sensitivity and specificity (Fagbemi and Guobadia 1995;Intapan et al 2003;Ghosh et al 2005;Yokananth et al 2005). Hence, on similar lines affinity chromatography was employed in the present study for the purification of specific immunodominant polypeptides against P. epiclitum.…”
Section: Resultsmentioning
confidence: 90%
“…However, till date no specific diagnostic polypeptide against P. epiclitum has been identified and purified. Affinity chromatography has been shown to be a very effective tool for isolation of candidate diagnostic and vaccine molecules (Ghosh et al 1999;Sharma et al 2001;Singh and Ghosh 2003;Yokananth et al 2005). The affinity purified antigens for Fasciola spp.…”
Section: Resultsmentioning
confidence: 99%
“…This study reports an assessment of two recombinant subunits of the antigen B, B1t and B2t, and the use of two new recombinant antigens, E14t and C317, in an ELISA for the detection of specific antibodies in UHD patients. For this study, we selected a well-characterized and extensive panel of sera that included sera from patients with UHD (n ϭ 102) confirmed by surgery; from patients with different parasitic diseases (n ϭ 68), especially those related to E. granulosus at the antigen composition level (alveolar hydatid disease, cysticercosis, teniosis, schistosomosis, fasciolosis, and nematodes) (7,18,30); and healthy donors (n ϭ 95). This latter group of individuals was chosen from an area free of E. granulosus, because healthy donors from areas in which E. granulosus is endemic could give rise to false-positive results from individuals who have been in contact with the parasite without developing the disease (32).…”
Section: Vol 15 2008 Serodiagnosis and Follow-up Of Hydatid Diseasementioning
confidence: 99%